Legalisation Process And Rights Of Persons Of Indonesian Descents (Pids) Residing In Mindanao, Philippines - Saleha, Putrie Agusti (2023)
This research study focuses on the legalisation process and rights of persons of Indonesian descent (PIDs) residing in Mindanao, Philippines, using the concepts of legalisation and push and pull theory. The study explores the challenges faced by PIDs in obtaining legal recognition and protection of their rights, and investigates the factors that influence their decision to stay in Mindanao even after obtaining Indonesian nationality. The research methodology utilized for this study involved conducting interview sessions and administering mini-questionnaires to collect primary data from PIDs who have undergone the legalisation process and obtained the status of Registered Indonesian Nationals (RINs). The collected data were analyzed using qualitative methods to identify patterns and themes.The findings of the study reveal that the legalisation process for PIDs in Mindanao, Philippines is arduous, involving navigating through bureaucratic procedures, documentation requirements, and legal complexities. PIDs face challenges related to language barriers, lack of knowledge about legal processes, and limited access to legal assistance, which pose significant barriers to their legalisation process. Despite these challenges, a significant number of PIDs obtain Indonesian nationality and become RINs. However, the study finds that many of them choose to remain residing in Mindanao even after obtaining Indonesian nationality. This phenomenon can be attributed to various push and pull factors. The push factors influencing the decision of PIDs to stay in Mindanao include economic challenges, lack of job opportunities, poverty, and social discrimination in Indonesia, which may discourage them from returning to their home country